Emerging new global soil governance structure in agrifood systems: Taking the “4 per 1,000” initiative as an example - Li, Li; Song, Xiaojing; Liu, Yang; Chai, Li (Frontiers in Sustainable Food Systems, 2023)
Food systems emit 21%-37% of the global greenhouse gases (GHGs). Soil degradation, accelerated by global warming, poses a threat to over 40% of the land surfaces, threatening food security. Keeping soils alive and healthy could not only play a part in food security, but also in sequestrating GHGs for climate mitigation. In 2015, the “4 per 1,000” Initiative was launched in Paris COP21, indicating that a “4‰” annual growth rate of the soil organic carbon sequestration could hold the temperature increase within 1.5°C−2°C. However, major GHG emitting countries haven't signed the 4‰ Initiative at national level. Political willingness need to be encouraged though institutional innovations in the global soil governance (GSG). This article conducts a comprehensive policy review for the 4‰ Initiative and attempts to develop the concept of global soil governance from an aspect of New Common But Differentiated Responsibility. The SOC sink targets reveal that countries like China, India, the UK, the US, and France take more pains than those like Australia, Russia, and Canada. A new “soil carbon rich” and “soil carbon poor” divide is perceived, which needs to be taken into the GSG as a restructuring motivation for setting a more practical and integrated framework. In that sense, some developed countries face similar challenges as the developing countries do, but could contribute more in finance and technology. Bandwagon of applying sustainable agricultural land management (SALM) methodology in carbon markets implies that soil-climate co-benefits get greater practical momentum with quantified trading platforms, which may stimulate potentiality if embodied in Article 6 of the Paris Agreement.